Python-based energy and exergy analysis for efficient evaluation of steam turbine performance - Muhammad Alvin Jordan; Fahrudin Fahrudin; Muchamad Oktaviandri (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Gas and Steam Power Plant (PLTGU) is a thermal power plant that has been in use since 1901. Over time, the energy and exergy analysis of PLTGU must be a fast analysis and takes very little time. This study aims to analyze the energy and exergy of one of the PLTGU components, namely the steam turbine using the python programming language, so that the analysis can be carried out quickly. As a theoretical basis to be able to carry out energy and exergy analysis of PLTGU steam turbines. The objects analyzed are: system input energy, isentropic efficiency, turbine work, energy loss rate, turbine energy efficiency, system exergy, fuel and product exergy, exergy destruction rate, and exergy efficiency. In carrying out the analysis, the theory used is the laws of thermodynamics 1 and 2. The results of the analysis are carried out according to the adopted theory, the isentropic efficiency of the steam turbine is in the range of to , the exergy of the system will always be greater than the energy of the system, the exergy of fuel is greater than product exergy, and the exergy efficiency of steam turbines is above . It can be concluded from this research, that the steam turbine can still be operated for the next few years.